Building Maintenance Management System for Heritage Museum - Othuman Mydin, Md Azree; Ismail, Siti Hajar; Md Ulang, Norhidayah (Eftimie Murgu University of Resita, 2012)
An investment in the building maintenance aspect is massive throughout the world. In most of the countries, it signifies approximately 50% of the entire revenue of the construction industry. The value of buildings depends on the eminence of the maintenance invested in them. Maintenance management engages obtaining utmost advantage from the investment made on the maintenance activities. At the moment, maintenance in buildings in Malaysia is on the increase in spite of size, category, location, and ownership. This study focuses on Building Maintenance Management System for Heritage Museum, which consists of two case studies in Penang State Museum and Art Gallery, Malaysia and Museum of Perak, Malaysia. The aim of this study is to propose methods to improve the maintenance management system for heritage museum. From the results, the common problem occurs during the implementation for the maintenance of each building is the budget for the maintenance and worker’s skill. The department of each museum must have their own maintenance unit to keep an eye on the maintenance activities for their buildings in order to improve the maintenance management system in their building.